3D Porous Fused Aromatic Networks for High Performance Gas and Iodine Uptakes. Issue 22 (24th October 2021) - Ahmad, Ishfaq; Noh, Hyuk‐Jun; Yu, Soo‐Young; Jeon, Jong‐Pil; Sun, Qikun; Mahmood, Javeed; Baek, Jong‐Beom
Abstract: Porous organic networks (PONs) are an emerging class of organic materials with 2D and 3D architectures formed by covalent bonds between light elements, such as C, H, N, O, and B. Extensive efforts have been devoted to synthesizing thermally "stable" 3D PONs to realize their practical applications. Here, the design and synthesis are reported for two new 3D PONs with fused aromatic structures. The PONs structures are constructed by the double condensation reaction between tetrapodal octaamine and pyrenetetraketone (PTK) or hexaketocyclohexane (HKH) to produce PTK‐PON (P‐PON) or HKH‐PON (H‐PON), respectively. The prepared nitrogen‐rich PONs show good thermal stabilities with specific surface areas of 873 m 2 g −1 (P‐PON) and 741 m 2 g −1 (H‐PON). Because of their relatively narrow pore dimensions (1.29 and 0.78 nm, respectively), the synthesized PONs exhibit high adsorption performance for small molecules such as carbon dioxide (CO2 ), hydrogen (H2 ), methane (CH4 ), and iodine (I2 ). Abstract : Two nitrogen‐rich porous organic networks (PONs: H‐PON and P‐PON) exhibit high adsorption performance for small molecules. A narrower pored H‐PON with a richer nitrogen content per volume has a stronger dipole–dipole interaction with CO2, resulting in a higher CO2 uptake. While a larger pored P‐PON shows high iodine uptake, due to larger pore volume.